Renal Impairment Caused by Statins in Rats Can be Restored by Thymoquinone - Hassan, Sherif S.; Thomann, Charity; Amin, Shaimaa N.; Youakim, Magdy; El-Shaarawy, Ehab A.A.; Ibrahim, Sara Shawky (Current Drug Discovery Technologies, 2025)
BackgroundAtorvastatin (ATO) is an HMG-CoA reductase inhibitor used to lower blood cholesterol, but it causes renal injury in high doses. Thymoquinone (TQ), is a natural antioxidant that has been shown to protect the kidney through its antiinflammatory, antioxidant, & antiapoptotic, effects.ObjectiveThe current study aimed to investigate whether posttreatment TQ could reverse ATO-induced renal injury, and the possible mechanism of action by which TQ produced such an effect.MethodsForty adult male rats were divided into 4 groups: (control; TQ-treated; ATO-treated; ATO plus TQ-treated). Blood and kidney tissue samples were tested for kidney functions, oxidative stress and apoptosis markers, and morphometric analyses of the histopathological and ultrastructural evaluations. Statistical analyses were done using JASP, Shapiro-Wilk, and Levene’s test. ANOVA and Kruskal-Wallis tests were done to determine differences between groups. The significance level was set at p<.05.ResultsThe ATO-treated group showed abnormal outcome measures including kidney functions, oxidative stress and apoptotic markers, and morphometric analyses of the histopathological and ultrastructural findings. Post-treatment TQ improved all outcome measures.ConclusionPosttreatment TQ could reverse oxidative stress-induced renal injury produced by high-dose ATO, suggesting a potential clinical application in patients with renal insufficiency with hypercholesterolemia.
Keywords: Atorvastatin